2019
DOI: 10.1155/2019/9659757
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrostatin-SN10 Ameliorates Pancreatitis-Induced Lung Injury by Affecting IL-6-Induced JAK2/STAT3-Associated Inflammation and Oxidative Stress

Abstract: Hydrostatin-SN1 (peptide sequence, DEQHLETELHTLTSVLTANGFQ), a kind of peptides extracted from snake venom, has been reported to have anti-inflammatory effect, but its truncated mutant hydrostatin-SN10 (peptide sequence, DEQHLETELH) on pancreatitis-induced acute lung injury has not been well documented. Interleukin- (IL-) 6-induced Janus Kinase 2/Signal Transducer and Activator of Transcription 3 (JAK2/STAT3) pathway is involved with inflammatory and oxidative stress activities and may be associated with the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…IL-6 is a proangiogenic, proinflammatory, and apoptotic cytokine and causes the pancreatitis-mediated lung injury and lethality. IL-6 mediated in innate and adaptive immune responses (Piao et al 2019 ). Severe COVID-19 associated pneumonia patients may exhibit features of systemic hyper-inflammation designated under the umbrella term of macrophage activation syndrome or cytokine storm (McGonagle et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a proangiogenic, proinflammatory, and apoptotic cytokine and causes the pancreatitis-mediated lung injury and lethality. IL-6 mediated in innate and adaptive immune responses (Piao et al 2019 ). Severe COVID-19 associated pneumonia patients may exhibit features of systemic hyper-inflammation designated under the umbrella term of macrophage activation syndrome or cytokine storm (McGonagle et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are a class of short noncoding RNA molecules that negatively regulate gene expression, thereby degrading their targeted mRNAs and inhibiting their transplantation [ 23 , 24 ]. JAK2 is a member of the Janus family of tyrosine kinases, which encodes a protein that is a nonreceptor tyrosine kinase and is involved in many important biological processes, such as cell proliferation, differentiation, apoptosis, and immune regulation [ 25 ]. In our study, we used TargetScan to predict that JAK2 was the target of miR-3133, and we confirmed this prediction.…”
Section: Discussionmentioning
confidence: 99%
“…International Publisher oxidative stress is implicated in the injury of acinar cells, as observed in a murine model of AP 7,8 . Moreover, clinical evidence has also shown that oxidative stress is common in the early phase in patients with AP 9 .…”
Section: Ivyspringmentioning
confidence: 96%